Mitral and tricuspid annuloplasty ring dehiscence: a systematic review with pooled analysis. (21st April 2021) - Arjomandi Rad, Arian; Naruka, Vinci; Vardanyan, Robert; Viviano, Alessandro; Salmasi, Mohammad Yousuf; Magouliotis, Dimitris; Kendall, Simon; Casula, Roberto; Athanasiou, Thanos
Summary:  : OBJECTIVES: Mitral and tricuspid ring annuloplasty dehiscence with consequent recurrent valve regurgitation is a rare but challenging procedural failure. The incidence and predisposing risk factors for annuloplasty ring dehiscence include technical and pathological ones. METHODS: A systematic database search with pooled analysis was conducted of original articles that only included dehiscence rate of mitral and tricuspid ring in EMBASE, MEDLINE, Cochrane database and Google Scholar, from inception to November 2020. The outcomes included were dehiscence rate in mitral and tricuspid, type of ring implanted, dehiscence rate by pathology and by ring size and shape. RESULTS: Our search yielded 821 relevant studies. Thirty-three studies met the inclusion criteria with a total of 10 340 patients (6543 mitral, 1414 tricuspid) of which 87 (mitral) and 30 (tricuspid) had dehiscence. Overall, dehiscence rate was 1.43%, diagnosed at a median of 4.5 ± 1.0 months postoperatively. A significant difference in mitral dehiscence rate was found by ring type (semi-rigid 1.86%, rigid 2.32%; flexible 0.43%; P  < 0.001). There was no significant difference in rate of dehiscence by ring size ( P  = 0.067) and shape in mitral ( P  = 0.281) but there was higher dehiscence rate in ischaemic compared to non-ischaemic mitral regurgitation (3.91% vs 1.63%; P  = 0.022). Among tricuspid studies, 9 of 10 studies did not report any dehiscence. CONCLUSIONS: Although rigid, semi-rigid and flexible annuloplasty rings provide acceptable valve repair outcomes, mitral annuloplasty ring dehiscence is clinically more common among rigid rings. Understanding the multifactorial nature of ring dehiscence will help in identifying the patients at high risk and improve their clinical outcomes.